2022
DOI: 10.3389/fcell.2022.955486
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-383: A tumor suppressor miRNA in human cancer

Abstract: Downregulated expression of anti-tumor miR-383 has been found in many kinds of cancer. MiR-383 family members can directly target the 3′-untranslated region (3′-UTR) of the mRNA of some pro-tumor genes to attenuate several cancer-related processes, including cell proliferation, invasion, migration, angiogenesis, immunosuppression, epithelial-mesenchymal transition, glycolysis, chemoresistance, and the development of cancer stem cells, whilst promoting apoptosis. Functionally, miR-383 operates as a tumor inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 142 publications
1
1
0
Order By: Relevance
“…In our study, we utilized a dual-luciferase reporter assay and FISH analysis to con rm the binding of miR-383-5p to circ_0007386. Our ndings align with previous reports on miR-383-5p (39), demonstrating its role in promoting apoptosis and inhibiting proliferation in NSCLC. The rescue experiments further corroborated circ_0007386's role as a sponge for miR-383-5p NSCLC progression.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we utilized a dual-luciferase reporter assay and FISH analysis to con rm the binding of miR-383-5p to circ_0007386. Our ndings align with previous reports on miR-383-5p (39), demonstrating its role in promoting apoptosis and inhibiting proliferation in NSCLC. The rescue experiments further corroborated circ_0007386's role as a sponge for miR-383-5p NSCLC progression.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, miR-7-5p, also downregulated in colorectal cancer tissues and cell lines, inhibits cell proliferation and migration by targeting Krüppel-like factor 4 (KLF4) [23]. Furthermore, miR-383-3p, which is downregulated in colorectal cancer tissues, functions as a tumor suppressor by targeting pro-tumor genes and is associated with tumor size, metastasis, and tumor stage [24]. The concurrent upregulation of lncRNA EVADR and the downregulation of these miRNAs in colorectal cancer suggests that EVADR may play a crucial role in the progression of the disease, potentially through its interactions with these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that miRNAs are important regulators of various cellular processes. In recent years, it has been widely studied in the occurrence and development of EC[ 48 - 51 ]. In this study, we used the Target Scan database to predict that mi-495-3p has a specific binding site in BUB1 mRNA 3′-UTR.…”
Section: Discussionmentioning
confidence: 99%